La cultura sin odio: una apuesta desde las Nuevas Juventudes Escolarizadas de Ciudad Bolívar, Bogotá, Colombia en contexto de pandemia - Carrillo-Pachón, Orlando; Vélez de la Calle, Claudia del Pilar (Educación y Ciudad, 2023)
The culture without hate has been one of the emerging categories that appear in the research process, showing how young people, despite being embedded in a traditionally violent society, express, as a general rule, the need to live in a peaceful society, without violence. The cases discussed here, although not all of them are directly involved in these events, do, by the fact of belonging to a young generation, belong to that group of individuals to whom a prejudice is created from the immoralization of youth, which has served, moreover, to act in a way that justifies a policy of hatred, of the vision of youth as a danger that can destabilize the traditions and "good" adult-adult-centric customs. The document is based on a qualitative research experience with the narrative methodological strategy with a group of 37 young people who, with their informed consent and under some pseudonyms, were able to express their opinions on various topics, such as violence and peace in their context. These are some of the reflections that have originated from this study.